A University-Based Construction of Asian Studies in Spain: Structural Analysis and Potential - Ramírez Ruiz , Raúl; Qiuyang, Li (Sinología hispánica. China Studies Review, 2026)
Asian Studies in Spain emerged in the late 1970s, driven by China’s reform and opening-up policy and Japan’s growing international influence, gradually evolving into a systematic academic field. This article examines the origins, development, and structural characteristics of Asian Studies in Spain, analyzing its contributions to Spanish cultural diplomacy and educational globalization, particularly in cultivating regional experts on Asia, attracting international students, and promoting Sino-Spanish cultural exchanges. It also explores the institutionalization process of Asian Studies in Spain and the challenges it faces. By comparing degree programs across different periods, the study reveals the evolution of Spain’s Asian Studies within the bachelor’s, master’s, and doctoral degree systems, highlighting the regional concentration and disciplinary diversity of its academic offerings.